KINERJA SUPERVISOR DAN KREATIVITAS GURU PAI - Pagga, Pagga; Getteng, Abd Rahman; Mustami, Khalifah; Syamsudduha, St (Idaarah: Jurnal Manajemen Pendidikan, 2020)
This study aims to determine the supervisor’s performance and the creativity of the Islamic Religious Education teachers at SMAN Sinjai Regency. This research used qualitative research. The data analysis technique used is data reduction, data presentation, data collection using descriptive exploratory analysis techniques, and inductive qualitative methods. The result was found that the supervisor’s performance in the preparation of supervisor program planning had been compiled in an accurate manner and the implementation of supervisor supervision had been implemented in the field continuously. PAI teacher creativity in SMA Negeri Sinjai Regency has increased through several programs that have been carefully prepared by supervisors. The supporting factors for supervisors in increasing the creativity of PAI teachers are the existence of supervisory standardization arrangements and the presence of collectors. As for the inhibiting factors for supervisors, namely the number of target schools that are too many, the busyness of the supervisors outside the supervision program, the number of supervisors is still low, and the teacher’s perception of supervision activities is still not good.